Transcriptional control of satiety in Caenorhabditis elegans. Issue 3 (4th May 2017) - Handley, Ava; Pocock, Roger
ABSTRACT: Obesity is an enormous worldwide health concern. Chronic illnesses associated with obesity include type-2 diabetes, hypertension, atherosclerosis and certain cancers. Communication between fat storage organs and the brain is essential for regulating feeding, metabolism and organismal activity—and hence obesity control. Model organism research provides opportunities to decipher conserved molecular mechanisms that regulate fat storage and activity levels, which is fundamental to understanding this disorder. We recently identified a transcription factor (ETS-5) that acts in specific neurons of the nematode Caenorhabditis elegans to control intestinal fat levels. Furthermore, we discovered a feedback mechanism where intestinal fat controls feeding and motor programs, similar to humans, where a sated stomach can inhibit feeding and induce lethargy. The precise molecular signals and neuronal circuitry underpinning brain-intestinal communication in C. elegans are however yet to be discovered. As most animals store surplus energy as fat, communication mechanisms that relay external information regarding food availability and quality, and internal energy reserves are likely conserved. Therefore, our identification of a neuronally-expressed transcriptional regulator that controls intestinal fat levels opens up new avenues of investigation for the control of metabolic disease and obesity.